CO2 CONTENT OF GREEK LIGNITE: THE CASE OF PROASTIO LIGNITE DEPOSIT IN PTOLEMAIS BASIN, NORTHERN GREECE - Metaxas Α.; Georgakopoulos Α.Ν.; Karageorgiou D.Μ.Μ.; Papanikolaou, G.; Karageorgiou, E.D. (Bulletin of the Geological Society of Greece, 2010)
Lignite is an important energy source for Greece, which severely relies on this fossil fuel for electricity generation over the years. The lignite combustion, however, releases a significant amount of carbon dioxide to the atmosphere per unit of energy generated, more than does the combustion of other fossil fuels. On the other hand, there is a growing concern over the possible consequences of global warming due to the increase of carbon dioxide in the atmosphere (a major greenhouse gas). Additionally, there is also a need for accurate estimates of carbon dioxide emissions. There are many factors resulting in the increase of CO2 content in lignite such as their formation and depositional environment, the possible presence of fossils, and their rank. In the present paper the CO2 content of the Proastio lignite deposit, Ptolemais Basin, is studied, in relation to the depositional palaeo-environment. An interpretation of CO2 variation with depth, age and surrounding rocks is also attempted. CO2 content of Proastio deposit is compared with this of other lignite deposits in the Ptolemais Basin, of various types and ages. Finally, the effect of CO2 content in the combustion of lignite is studied, while the possibility of the geological storage of the emitted carbon dioxide is explored after its capture from the Thermal Power Plants (CCS technology).